Microcomputer development system FT 68K - Cong, Nguyen Chi; Thuan, Tran Xuan (Journal of Computer Science and Cybernetics, 2015)
A microcomputer development System named FT 68K has been developed at the Institute of Informatics and Cybernetics, Hanoi. Based on the microprocessor MC 68000 the FT 68K is running under the Operating System CP/M 68K and its service allows an implementing of the Operating System UNIX. This paper also discusses its design philosophy and some experiences from the use of the FT 68K, which is open to a next extension.